Evaluation and Design of Power Controller of Two-Axis Solar Tracking by PID and FL for a Photovoltaic Module - Joel J. Ontiveros; Carlos D. Ávalos; Faustino Loza; Néstor D. Galán; Guillermo J. Rubio (International Journal of Photoenergy)
Solar trackers represent an essential tool to increase the energy production of photovoltaic modules compared to fixed systems. Unlike previous technologies where the aim is to keep the solar rays perpendicular to the surface of the module and obtain a constant output power, this paper proposes the design and evaluation of two controllers for a two-axis solar tracker, which maintains the power that is produced by photovoltaic modules at their nominal value. To achieve this, mathematical models of the dynamics of the sun, the solar energy obtained on the Earth’s surface, the two-axis tracking system in its electrical and mechanical parts, and the solar cell are developed and simulated. Two controllers are designed to be evaluated in the solar tracking system, one Proportional-Integral-Derivative and the other by Fuzzy Logic. The evaluation of the simulations shows a better performance of the controller by Fuzzy Logic; this is because it presents a shorter stabilization time, a transient of smaller amplitude, and a lower percentage of error in steady-state. The principle of operation of the solar tracking system is to promote the orientation conditions of the photovoltaic module to generate the maximum available power until reaching the nominal one. This is possible because it has a gyroscope on the surface of the module that determines its position with respect to the hour angle and altitude of the sun; a data acquisition card is developed to implement voltage and current sensors, which measure the output power it produces from the photovoltaic module throughout the day and under any weather conditions. The results of the implementation demonstrate that a Fuzzy Logic control for a two-axis solar tracker maintains the output power of the photovoltaic module at its nominal parameters during peak sun hours.